Effect of Return on Asset, Debt Equity Ratio and Current Ratio on Company Value (Study on Manufacturing Companies Listed on Indonesia Stock Exchange for the Period 2017-2020) - Noegroho, Novianto; Ariefiantoro, Teguh; Suryawardana, Edy (Universitas Semarang, 2022)
The purpose of this study is to examine the effect of Profitability proxied by ROA, Working Capital Proxied by Debt Equity Ratio and Liquidity Proxied by current Ratio to the potential for Firm Value in the company. The sample used in this study is various manufacturing companies listed on the Indonesia Stock Exchange during the period 2017 to 2020. The sample selection method used was the purposive sampling method. Hypothesis testing is done using logistic regression. Based on the results of hypothesis testing it can be concluded that the Return On Asset variable is proven to have a significant positive effect on the likelihood of Firm Value, the Debt Equity Ratio Variable is proven to have a significant negative effect on the likelihood of Firm Value, as well as the Current Ratio variable also has a significant Positif effect on the likelihood of firm Value.